Ketone production in children with type 1 diabetes, ages 4–14 years, with and without nocturnal insulin pump suspension. Issue 6 (12th July 2016) - Wadwa, R. Paul; Chase, H. Peter; Raghinaru, Dan; Buckingham, Bruce A.; Hramiak, Irene; Maahs, David M.; Messer, Laurel; Ly, Trang; Aye, Tandy; Clinton, Paula; Kollman, Craig; Beck, Roy W.; et al.
Abstract : Objective: To compare the frequency of elevated morning blood ketone levels according to age in 4–14 year olds with type 1 diabetes following overnight use of an automated low glucose insulin suspension system, or following control nights when the system was not used. Research design and methods: For 28 children ages 4–9 years and 54 youth ages 10–14 years, elevation of morning blood ketone levels was assessed using the Precision Xtra Ketone meter following 1155 and 2345 nights, respectively. Repeated measures logistic regression models were used to compare age groups for blood ketone level elevation following control nights (system not activated) and following intervention nights with and without insulin suspension. Results: Elevated morning blood ketones (≥0.6 mmol/L) were present following 10% of 580 control nights in the 4–9 year olds compared with 2% of 1162 control nights in 10–14 year olds ( P < 0.001). Likewise, the frequency was greater following intervention nights in the younger age group (13% of 575 nights vs 2% of 1183 nights, P < 0.001). A longer duration of pump suspension resulted in a higher percentage of mornings with elevated blood ketones in the younger age group ( P = 0.002), but not in the older age group ( P = 0.63). The presence of elevated morning ketone levels did not progress to ketoacidosis in any subject. Conclusions: Elevated morning blood ketones are more common in younger children with type 1 diabetes with or without nocturnal insulin suspension. Care providers need to be aware of the differences in ketogenesis in younger age children relative to various clinical situations.